Kesadaran Gender Remaja Ditinjau Berdasarkan Jenis Kelamin dan Implikasinya bagi Layanan Bimbingan dan Konseling - Mutiara Haya (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2023)
The purpose of this study is to describe the differences in the level of gender awareness based on sex and analyze the effect of these comparisons on education and its implications for guidance and counseling. The method used in this study was systematic literature review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The data used in this study are journal articles obtained from scientific article database applications such as Scopus and Google Scholar. The result from the systematic literature review is that there are differences in the level of gender awareness and the level of awareness of other things between girls and boys. The differences of the gender awareness level are influenced by the social environment and if its not developed, theres will be gender gaps and biases that can disadvantages one of gender.